TEOREMA SEGITIGA SIKU – SIKU DALAM PERBANDINGAN ENERGI RELATIVISTIK (Universitas PGRI Sumatera Barat, 2022)
Physics is a branch of scientific knowledge that requires understanding other disciplines, such as mathematical concepts. As for the development of increasingly advanced technology, it affects the world of education such as the implementation of CBT (Computer Based Test). Based on this, of course, innovation is needed to solve physics problems in a short and easy time. One example of material taught in physics that can be done in an easier way is material on special relativity. The solution to the problem of Einstein's special relativity, especially the comparison of relativistic energy, can use a right triangle by fulfilling the Pythagorean equation. This study describes the analysis of the right triangle theorem with the relativistic energy comparison equation.